2019
DOI: 10.1101/611293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does parental angling selection affect the behavior or metabolism of brown trout parr?

Abstract: Acknowledgements 21We thank the staff of Kainuu Fisheries Research Station for their help in catching, breeding 22 and rearing fish, Dr. Hannu Huuskonen for advice in setting up the respirometry, and Dr. 23Chris Elvidge for comments on the manuscript. J.M.P., Abstract 27The behavior of organisms can affect their vulnerability to human induced selection, 28 including recreational angling. Angling is expected to select fish with bold behavior, which 29 may be linked to low stress responses through stress coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…Other studies in salmonids have found sex differences in the performance of 2+ yearold or mature individuals, including a higher aerobic scope, but not SMR, and a higher cost of swimming in males than in females (Clark et al 2011;Makiguchi et al 2017;Archer et al 2020). The lack of sex differences in metabolic phenotypes in our study both across and within age-at-maturity genotypes, therefore, supports the conclusion that sex-dependent lifehistory variation is not reflected in metabolic rates during the juvenile stage, as suggested by a few other studies (Regnier et al 2015;Prokkola et al 2021;Åsheim et al 2021). Recently, it was also shown that salmon females have a higher size threshold for maturation after one year at sea compared to males (Tréhin et al 2021), and further studies are required to link the performance differences and sex-specific maturation schedules of salmon at sea.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies in salmonids have found sex differences in the performance of 2+ yearold or mature individuals, including a higher aerobic scope, but not SMR, and a higher cost of swimming in males than in females (Clark et al 2011;Makiguchi et al 2017;Archer et al 2020). The lack of sex differences in metabolic phenotypes in our study both across and within age-at-maturity genotypes, therefore, supports the conclusion that sex-dependent lifehistory variation is not reflected in metabolic rates during the juvenile stage, as suggested by a few other studies (Regnier et al 2015;Prokkola et al 2021;Åsheim et al 2021). Recently, it was also shown that salmon females have a higher size threshold for maturation after one year at sea compared to males (Tréhin et al 2021), and further studies are required to link the performance differences and sex-specific maturation schedules of salmon at sea.…”
Section: Discussionsupporting
confidence: 89%
“…We used fish from two originally philopatric populations, one captured from the wild, the other reared in a hatchery for stocking purposes for over five decades, and their reciprocal F1 crosses. Previous studies have demonstrated that these strains differ in personality traits and in migration tendency (Alioravainen et al 2018, Prokkola et al 2019, Lemopoulos et al 2019b) the hatchery strain being the boldest and the most migratory. Here, we hypothesized that the experimental populations would be strongly diverged in their behaviour, and that the hatchery population would represent a more (downstream) dispersive phenotype and display higher day-time activity than the wild strain.…”
Section: Introductionmentioning
confidence: 98%